Is the National Institute for Health and Care Excellence (NICE) in England more ‘innovation-friendly’ than the Federal Joint Committee (G-BA) in Germany? - Schäfer, Ramon; Schlander, Michael (Expert review of pharmacoeconomics and outcomes research, 2018)
Objectives: Our study explores whether, and how, different methodological choices are associated with different health technology assessment (HTA) outcomes. We focus on the Federal Joint Committee (Gemeinsamer Bundesausschuss, G-BA) in Germany and the National Institute for Health and Care Excellence (NICE) in England. Both agencies may be considered as exemplars for the application of the principles of evidence-based medicine and the logic of cost-effectiveness, respectively.Methods: We extracted data from all publically available G-BA appraisals until April 2015, as well as all NICE single technology appraisals completed during this period. We compared HTA results for matched condition-intervention pairs by G-BA and NICE, and explored other factors including therapeutic area, clinical effectiveness and cost-effectiveness.Results: NICE issued guidance for 88 technologies (125 subgroups) and recommended 67/88 technologies (99/125 subgroups). G-BA completed 105 appraisals (226 subgroups) and determined additional benefit for 64/105 appraisals (90/226 subgroups). We identified 37 matched pairs; for 24/37 drugs, evaluations diverged. NICE recommended 78% (29/37) of technologies appraised, whereas G-BA confirmed additional benefit for 57% (21/37) only (p < 0.05).Conclusions: NICE evaluates new drugs more favorably than G-BA. However, our analysis suggests differences by therapeutic area. Results indicate that different methods are associated with systematic differences in HTA outcomes.